Hanessian-Hullar reaction in the synthesis of highly substituted trans-3, 4-dihydroxypyrrolidines: Rhamnulose iminosugar mimics inhibit α-glucosidase. Issue 1 (3rd January 2020) - Liu, Zilei; Yoshihara, Akihide; Jenkinson, Sarah F.; Wormald, Mark R.; Kelly, Ciarán; Heap, John T.; Marqvorsen, Mikkel H.S.; Estévez, Ramón J.; Fleet, George W.J.; Nakagawa, Shinpei; Izumori, Ken; Nash, Robert J.; et al.
Abstract: The key step in the syntheses of highly substituted trans -3, 4-dihydroxypyrrolidines is introduction of bromide by stereospecific and regiospecific Hanessian-Hullar reactions; benzylidene lactones of l -rhamnonolactone and 6-deoxy-this should be small unnpercase d not l why can I not correct this-gulonolactone allow introduction of N at C2 with inversion or retention of configuration. Initially a protecting group, the benzylidene acetal then provides a bromide at C5 to allow formation of the pyrrolidine ring. With silyl protecting groups, bromide was introduced at C5 with inversion of configuration whereas benzoyl protection gave a mixture of retention and inversion, indicative of neighbouring group participation in a Hanessian-Hullar reaction. Four stereoisomeric pyrrolidines - iminosugar mimics of α- and β-l -rhamnulose and α- and β-6-deoxy-d -sorbose were prepared. Only the α-l -rhamnulose mimic showed moderate inhibition of rhamnosidase but some were good inhibitors of α-glucosidases; none inhibited rhamnose isomerase and they had a small effect as synthetic inducers of the rhamnose catabolic operon in E. coli . Graphical abstract: Image 1 Highlights: Iminosugar mimics of l -rhamnulose inhibit α-glucosidases but not rhamnose isomerase. Benzylidene protection then allows a stereospecific and regiospecific activation. Benzoate causes neighbouring group participation in Hanessian-Hullar reactions. Easy efficient synthesis of highly functionalised pyrrolidines. Search for control of rhamnulose and rhamnose metabolising enzymes.